Energetic ion losses 'channeling' mechanism and strategy for mitigation. (27th June 2019) - Nabais, F; Bizarro, João P S; Borba, D; Coelho, R; Ferreira, J; Figueiredo, A; Fitzgerald, M; Hellesen, C; Kiptily, V; Mantsinen, M; Portugal, F; Rodrigues, P; et al.
Abstract: Results from two different sets of JET experiments are presented. In experiments in which toroidicity-induced Alfvén eigenmodes (TAEs) localized at different radial locations had the same frequencies and toroidal mode numbers, the occurrence of enhanced losses after the excitation of TAEs in the core of the plasma was observed. On the contrary, enhanced losses were not observed if the TAEs localized at different radial locations had different frequencies and toroidal mode numbers. Numerical modeling indicates that, in the first set of experiments, the enhanced losses were caused by a combined effect of the TAEs localized at different radial locations. The TAEs localized in the plasma core transported energetic ions from the core to outer regions of the plasma. Then, the TAEs localized in outer regions of the plasma interacted with these ions just transported by the core-localized TAEs causing a further radial displacement of the ions to the plasma edge. This process eventually ends up causing the loss of the resonant ions. In the second set of experiments, it was found that TAEs localized in the plasma core and in outer regions did not interact with the same ions and so no enhanced losses were measured. Sheared profiles of the safety factor combined with flat mass density profiles lead to larger differences on the frequencies of the TAEs localized at different radial locations, eventually avoiding loss of energetic ions through the described mechanism.